Psikoedukasi Pencegahan Dan Penanganan Perilaku Bullying Berbasis Ekologi Pada Guru Sekolah Dasar - Muhibbin, Maulana Arif; Suharsono, Riyanto Setiawan (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The following bullying behaviors are prevalent in primary schools: relationship bullying, physical bullying, and verbal bullying. Bullying has a detrimental effect on the mental health of witnesses, offenders, and victims. Issues occur when educators lack a thorough understanding of how to deal with and stop bullying in the classroom. Therefore, a comprehensive strategy is required to end the cycle of bullying in schools. Training in managing and preventing bullying incidents based on Bronfenbrenner's ecological theory for teachers is the suggested remedy for the issue. The idea of ecology is highly applicable to combating bullying by getting involved in many facets of the school environment. Teachers at SD Muhammadiyah 1 Jember are the service's target audience. The planned activities carried out are teacher training and mentoring. Activities are carried out using workshop methods, pre-test and post-test, focus group discussions using learning technology media. Through this activity, it is hoped that teachers can understand and implement case prevention and handling in schools. The results of the service post test showed an increase in teachers' understanding of the implementation of Bronfenbrenner's ecology to build a bullying-free school ecosystem. Furthermore, ongoing assistance is needed to form an anti-bullying task force in Bronfrenbrenner ecological-based schools.ABSTRAKTrend perilaku bullying yang sering terjadi di Sekolah Dasar adalah bullying verbal, bullying fisik dan bullying relasi. Perilaku bullying berdampak buruk bagi kesejahteraan psikologis korban, pelaku dan saksi. Permasalahan muncul ketika guru belum sepenuhnya mengetahui mekanisme penanganan dan pencegahan perilaku bullying di sekolah. Dengan demikian perlu adanya pendekatan holistik untuk memutus mata rantai perilaku bullying di sekolah. Solusi permasalahan yang ditawarkan adalah pelatihan penanganan dan pencegahan kasus bullying berbasis teori ekologi Bronfenbrenner pada guru. Konsep ekologi cukup relevan untuk mengatasi bullying melalui partisipasi seluruh tingkatan ekosistem sekolah. Target sasaran dalam pengabdian ini adalah guru SD Muhammadiyah 1 Jember. Rencana kegiatan yang dilakukan adalah pelatihan dan pendampingan Guru. Kegiatan dilaksanakan dengan metode workshop, pre test dan post test, focus group discussion dengan memanfaatkan media teknologi pembelajaran. Melalui kegiatan ini diharapkan guru dapat memahami dan mengimplementasikan pencegahan dan penanganan kasus di sekolah. Hasil post test pengabdian menunjukkan peningkatan pemahaman guru tentang implementasi ekologi Bronfenbrenner untuk membangun ekosistem sekolah bebas bullying. Selanjutnya, perlu dilakukan pendampingan yang berkelanjutan untuk membentuk satgas anti perundungan di sekolah berbasis ekologi Bronfrenbrenner.